Environmental and Genetic Variation for Yield-Related Traits of Durum Wheat as Affected by Development - Giunta, Francesco; De Vita, Pasquale; Mastrangelo, Anna M.; Sanna, Gavino; Motzo, Rosella (Frontiers in Plant Science, 2018)
Phenology has a profound effect on adaptation and productivity of crops. The impact of phenology on tillering and fertility traits of durum wheat (Triticum turgidum L. subsp. durum Desf.) was evaluated with the aim of specifying which group of flowering genes (Vrn, Ppd or eps) was involved in their control. A recombinant inbred line population was grown under four contrasting conditions of vernalisation and daylength. Phenotyping was carried out according to robust phenological models dissecting both phenological and yield related traits. Whole-genome profiling was performed using the DArT-Seq technology. The genetic variability for tillering was mainly related to the genetic variability for vernalisation sensitivity, as shown by the many quantitative trait loci (QTLs) identified in non-vernalised plants associated to both tillering and phenological traits. No effects of photoperiod sensitivity on spikelet number were detected in short-day-grown plants, apparently because of limited genetic variability in photoperiod sensitivity of the population. Earliness per se was involved in control of spikelet number via final leaf number, with these traits genetically correlated and sharing some QTLs. Chaff weight and number of kernels per g chaff were negatively associated and related to anthesis date under most conditions. QTL mapping uncovered novel loci involved in phenological control of tillering and fertility traits, and confirmed the presence of several well-established loci. Phenotyping of both phenology and kernel number according to a robust physiological model amplified the possibility of identifying genetic factors underlying their variations. Also, isolating known flowering gene cues by manipulation of environmental conditions provided the opportunity for each group of genes to be expressed without confounding effects of the others. This information helps to predict the consequences of either genetic manipulation of flowering genes and changes in environmental conditions on the potential yield of durum wheat.